MASALAH SOSIAL: KEMISKINAN DAN KEJAHATAN DALAM NOVEL MARYAMAH KARPOV KARYA ANDREA HIRATA - Gayo, Gunter Ary; Satini, Ria; Nisja, Indriani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Poverty is a condition in which a person cannot meet basic needs. There are several reasons for poverty, such as a lack of resources to meet basic needs or difficulty obtaining education and employment. The purpose of this study is to describe social problems such as crime and poverty found in Andrea Hirata's novel Maryamah karpov. This study uses a qualitative descriptive analysis method. The data consists of quotations from the novel text that show the types of poverty and crime experienced by the main character Ikal, and the surrounding community. The results of the study show that poverty in the novel is depicted as an economic obstacle that impacts access to education, the fulfillment of basic needs, and injustice in the work system. Meanwhile, crime is depicted as oppression, physical and psychological violence, and racial discrimination experienced by Ikal and other characters in the novel, both in the workplace and in educational institutions. The latest finding of this study is the disclosure of the relationship between poverty and crime as a representation of social inequality that is relevant to Indonesian society today. Andrea Hirata's novel Maryamah Karpov is a sharp social critique of an unfair social system, especially in remote areas such as Belitung.